2020
DOI: 10.18632/oncotarget.27568
|View full text |Cite
|
Sign up to set email alerts
|

CD44+/EPCAM+ cells detect a subpopulation of ALDHhigh cells in human non-small cell lung cancer: A chance for targeting cancer stem cells?

Abstract: Objectives: Several studies demonstrated that aldehyde dehydrogenase (ALDH) and CD44 are the most considered cancer stem cells (CSC) markers. However, a comparison between ALDH high cells and CD44+ cells have been previously described with no significant correlation. Indeed, the aim of the present research is to identify a superficial marker able to match with ALDH high cells population in freshly isolated human lung cancer cells. Materials and Methods: This cross-sectional study analyzed the expression of ALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…More recently, Masciale et al [ 28 ] have identified and isolated lung CSCs from primary tumors based on ALDH expression, demonstrating their high capacity to form in vitro tumor spheres. Additionally, the results in adenocarcinoma and squamous cell carcinoma of the lung showed that the cells successfully grew for three weeks in a serum-free medium, forming spheres and overexpressing stemness genes, i.e., SOX2 and NANOG [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Masciale et al [ 28 ] have identified and isolated lung CSCs from primary tumors based on ALDH expression, demonstrating their high capacity to form in vitro tumor spheres. Additionally, the results in adenocarcinoma and squamous cell carcinoma of the lung showed that the cells successfully grew for three weeks in a serum-free medium, forming spheres and overexpressing stemness genes, i.e., SOX2 and NANOG [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Masciale et al. have suggested that there is a subpopulation of cells CD44+/EpCAM+ with a high correlation with ALDH high cell populations ( 49 ) which were previously shown to be cancer stem cells in NSCLC patients ( 48 ). A marker like ALDH for cancer stem cells has also been identified and described by many scientists ( 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…These identification markers may be subjected to genetic modifications and identify specific CSCs subpopulations with different molecular characteristics. For example, the upregulated ATP-binding cassette (ABC) transporter G subfamily (ABCG), absence or presence of mutated NOTCH1, or different isotypes as observed for CD44v [ 33 , 52 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different markers for CSCs have been studied in the last recent decades, and scientists tried have attempted to improve the identification of this better this subpopulation by using a double or triple marker [ 15 , 32 , 33 , 65 70 ]. Masciale et al reported a novel subpopulation of cells expressing CD44+/epithelial cell adhesion molecule (EpCAM + ) that was positively correlated with ALDH+ cells [ 33 ]. They compared two similar CSC populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation